Investigation of ultrastructure and texture changes of fillets of rainbow trout grown under different aquaculture systems: Structural comparison of trout fillets in different aquaculture systems - Demirkale, İbrahim (Cellular and Molecular Biology, 2023)
In this study, the physical structure of fillets of rainbow trout (Oncorhynchus mykiss) grown under different aquaculture conditions was compared. For this purpose, scanning electron microscopy (SEM) analysis, texture profile (hardness, springiness, cohesiveness, gumminess, chewiness), and color measurements (L, a, b, chroma, hue and whiteness) of the fillets of trout taken from two different aquaculture environments were examined. When the texture profile of fillets taken from both environments was compared, it was determined that the hardness (40.30–69.80 N), gumminess (26.85–41.89 N) and chewiness (25.37–36.82 N) values of the fish samples taken from the extensive culture were higher than the samples taken from the recirculated system. The difference between other values was not found to be significant. In parallel with the hardness results, when the SEM images were examined, it was determined that the fillets of the fish taken from the extensive system had a thicker fibril ultrastructure than those from the RAS. The variable environmental parameters and aquaculture duration were observed to have an effect on muscle development, and that especially the long breeding period in the extensive system has a positive effect on the meat structure of the fish. Cultivation in different environments was not determined to have a significant effect on the color values of either the skin or fillet samples. As trout is the leading fish in freshwater production, it is very important for aquaculture to determine the physical changes in the flesh structure of trout according to the growing conditions.